Unlocking Tacloban's potential consumer demand and influential factors in expanding leisure investments for vibrant tourism - Capon, Cates Angelic Y.; Garcia, Jian Marish G.; Verra, Dirck S.; Dacuyan, Flordeliz B. (Tacloban City Division of Management, University of the Philippines Tacloban College, 2024)
This study aims to evaluate the prevailing demand for leisure-oriented businesses in Tacloban City and its impact on entrepreneurs' decision-making regarding the expansion of leisure-oriented investments. A mixed-method design, primarily qualitative in nature, was employed. Qualitative data was collected from Tacloban City entrepreneurs, while quantitative data was obtained from the consumer demand for leisure-oriented goods and services in Tacloban City. The findings reveal that entrepreneurial drive in Tacloban City's tourism sector is characterized by a multifaceted approach that prioritizes understanding and meeting the diverse demands of consumers within the leisure industry. Entrepreneurs actively assess market dynamics, consumer needs, and opportunities for expansion. However, they face limitations such as infrastructural deficiencies, insufficient external support, and a lack of strategic branding. External support and collaboration among stakeholders are essential for overcoming these limitations and fostering sustainable growth. The study concludes that passion for local tourism is the driving force among entrepreneurs that encourages their commitment to showcasing the city's unique identity and contributing to its growth as a vibrant destination. By leveraging external support and collaborative efforts, Tacloban City can create a thriving tourism industry that caters to evolving consumer demands, contributing to economic development and job creation. Recommendations include maximizing efforts of the Local Government Unit, fostering collaboration among stakeholders, and providing financial support and investment opportunities to entrepreneurs.
Undergraduate thesis (Bachelor of Science in Accountancy)-- University of the Philippines Tacloban.
Keywords: Entrepreneurship -- Tacloban City; Consumer demand; Leisure; Vibrant tourism